2015
DOI: 10.1590/1982-0194201500094
|View full text |Cite
|
Sign up to set email alerts
|

Repercussões no cotidiano dos pacientes pós-transplante cardíaco

Abstract: Objective: To learn the repercussions on the daily living of patients that underwent heart transplantation. Methods: A descriptive and qualitative study was conducted in a transplantation center in the Brazilian Northeast region. Nine patients who underwent heart transplantation participated in the study. Data were collected using the focus group technique, facilitated in four meetings. The excerpts of their statements resulted in two thematic categories: being a heart transplantation patient -before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Studies have shown that patients achieve significant improvements in their quality of life when they have greater social, family and spiritual support [6] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that patients achieve significant improvements in their quality of life when they have greater social, family and spiritual support [6] .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore indicated for those patients with worse prognosis and without alternatives of clinical treatments [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment adherence behavior may be affected by the presence of other associated comorbidities and limitations, which may contradict the patient's expectations of overall medical improvement upon transplantation, thereby directly affecting adherence rates. Perception of transplantation as a modality of treatment, not a cure, may lead patients away from recognizing its positive effects and reduce patient motivation regarding treatment over the post-transplantation period, (36) which in turn contributes to the high non-adherence rate seen in this study.…”
Section: Discussionmentioning
confidence: 94%
“…(33) Given the family and social setting can be characterized as a significant support network, it is possible to suggest that related variables can directly affect an individual's life and consequently, their adherence. (36) The consequences of IMS NA are multiple. For patients, they include some of the worst transplantation prognoses, with an increase in rejection rate, graft loss, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for care that will make subjects the protagonists of their own health is relevant, above all when this care is provided to patients who need to change habits, such as is the case with heart transplant patients. The complexity of the changes involving the transplant cause alterations in the transplanted individual's usual life style and may directly affect their well-being (3) . In these cases, nursing care needs to go beyond guaranteeing survival, it is necessary to transcend to the pursuit of quality of life during that survival.…”
Section: Introductionmentioning
confidence: 99%